Evaluation of tidal stream energy at major tidal inlets of Goa, India. (1st November 2022) - Mendi, Vikas; Seelam, Jaya Kumar; Rao, Subba
ABSTRACT: An attempt has been made to identify promising sites for tidal stream energy assessment along the Goa coast on central west coast of India. A two-dimensional tidal-driven validated numerical model is used to assess the tidal stream velocities. The numerical model results are further used to estimate the tidal stream energy over the simulation period which would form a resourceful input for future to optimize locations of tidal energy farms. The locations of current maxima in each of the tidal driven regions have been identified and the energy is estimated thereof. This paper describes the tidal driven currents using a numerical model and their validation with measurements; and estimation of tidal stream energy among the different selected locations to choose the most feasible location for tidal energy extraction along Goa coast.